2020
DOI: 10.1016/j.jad.2020.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID-19 pandemic in the Philippines

Abstract: Highlights Students report moderate-to-severe psychological impact of the COVID-19 pandemic. Timely and adequate health information has protective psychological effect. Health care workers are less likely to be psychologically affected. Home quarantine is associated with depression, anxiety and stress symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

46
509
11
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 494 publications
(582 citation statements)
references
References 23 publications
46
509
11
16
Order By: Relevance
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies have suggested that experiencing a severe infectious disease epidemic increases the prevalence of mental health issues, [12][13][14][15][16][17][18][19][20][21][22] it is difficult to find relevant literature or empirical studies that explore quarantine hotel employees faced with the challenge of psychological resilience. Therefore, this study aims to investigate the mental health status and psychological impact on quarantine hotel employees during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Each subscale contains seven items, and is scored using a 4-point Likert scale ranging from 0 (did not apply to me at all) to 3 (much or mostly applied to me). The depression subscale consists of questions 3, 5, 10, 13, 16, 17 and 21, and the score ranges are as follows: normal/no depression (0-9), mild depression (10-13), moderate depression (14)(15)(16)(17)(18)(19)(20), severe depression (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28 and above). The anxiety subscale consists of questions 2, 4, 7, 9, 15, 19, and 20, and the score ranges are as follows: normal/no anxiety (0-7), mild anxiety (8)(9), moderate anxiety (10)(11)(12)(13)(14), severe anxiety (15)(16)(17)(18)(19), and extremely severe anxiety (20 and above).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health is 1 out of 10 most studied topic pertaining to COVID-19 (Tran et al, 2020). Internationally, plethora of studies have explored the impact of COVID-19 on mental health among different populations and found significant psychological distress driven by the pandemic (Dang et al, 2020;Tee et al, 2020;Wang, Pan, et al, 2020a;Xiong et al, 2020). Several papers from China have reported that the general public have experienced a great deal of anxiety, depression, an increased consumption of alcohol, and sleep problems (Ahmed et al, 2020;Qiu et al, 2020, Wang, Chudzicka-Czupala, et al, 2020Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But the ratio of participants experience anxiety using CPAS-11 is higher than the 13.84% identified as experiencing severe anxiety using GAD-7, which has been used to measure anxiety of Filipinos during the COVID-19 pandemic in at least one previous study (Bernardo & Mendoza, 2020). The ratio is also higher than the 11.07% of the respondents experienced severe to extremely severe anxiety using the anxiety subscale of the Depression, Anxiety, and Stress Scale (DASS-21;Lovibond & Lovibond, 1995) in another study (Tee et al, 2020) involving a Filipino sample. One might infer that the CPAS-11 is picking up Filipino participants' anxiety symptoms that were not being screened by more general measures of anxiety like GAD-7 or DASS-21.…”
Section: Discussionmentioning
confidence: 94%